Ideal Couple in the Koran Buya Hamka's Perspective - Fauziyah; Moh. Jufriyadi Sholeh (Values: Jurnal Kajian Islam Multidisiplin, 2025)
It has been made clear in this Qur'an that Allah has created all things in pairs of man or in the earth. He created man and woman in pairs, that is to create a prayer in a marriage, and every couple must want to have an ideal couple. But not very often found is divorce, KDRT is done by a couple so that it creates non-military inequalities in family life. Of some of these problems, this research is aimed at finding out any signs that talk about an ideal couple. Second: The punishment of Hamka concerning the ideal couple in the Qur'an. This study uses a qualitative approach to library research with descriptive analytical methods. Of some of the verses concerning the husband of his wife: QS. Al-Baqarah: 187, QS. Al-Furqa>n: 74, QS. An-Nisa': 19, QS. An-Nisa: 34 and QS. Al-Baqarah: 223. Second: Buya Hamka explains in her book that a husband's tendency to have an ideal wife who is passionate about mercy as well as his wife so that he can make a path in the balance of his family and home life.